Divergent demographic responses of boreal-breeding ducks to growing season variability - David J. Messmer; Stuart Slattery; Mark C. Drever; Chris Derksen; Robert G. Clark (Oecologia, 2026)
In seasonal environments climatic variability shapes the timing, duration, and magnitude of primary production with effects that may percolate upward through food chains. While the role of spring phenology and implications of trophic mismatches have been documented in some bird species, including waterfowl, there is little research on the role of growing season duration or overall productivity. Duck species breeding in the western boreal forest (WBF) of North America vary widely in their average timing and plasticity for breeding dates, which may set up differing sensitivity to spring phenology. In contrast, increases in growing season duration and productivity may positively impact species regardless of life history through the extension of the breeding season and bottom-up trophic enrichment. We tested these hypotheses using breeding population estimates for 8 species (or species groups) of ducks and normalized difference vegetation index to infer spring phenology, length of growing season, and growing season productivity for duck survey areas in the WBF, 1982–2019. Spring phenology had mixed effects on species’ population growth rates, and effects were generally not consistent with mediation by average breeding dates or plasticity. Length of season and productivity effects showed some species’ population growth rates decreasing following longer seasons or higher productivity, opposite our predictions. These results suggest that, for secondary consumers like ducks, the role of growing season characteristics may be mediated or superseded by more complex biotic and abiotic interactions than can be explained with simple annual summaries of growing season characteristics.

Shared population trends but no annual synchrony in duck species across Europe and North America - David J. Messmer; Matthieu Guillemain; Mark C. Drever; Tom Langendoen; Robert G. Clark (European Journal of Wildlife Research, 2025)
Few studies have explored population dynamics of species sharing life-history traits and common environmental drivers but living in widely separated regions or continents. Large-scale climate cycles can impact habitats and populations over broad geographic areas and may act as global forces shaping animal population dynamics. We tested for synchronous population dynamics of eight ecologically equivalent duck species in Western Europe (WEU) and central North America (NA) from 1976 to 2019. We investigated the extent to which the Atlantic Multi-Decadal Oscillation (AMO) may have induced shared climatic conditions on the breeding areas of these populations and whether the index was correlated with duck population dynamics. Evidence of annual and long-term population synchrony was assessed by estimating correlation in annual growth rates and population abundances, respectively. Shared (increasing) long-term trends in WEU and NA were found in four species-pairs, but no species-pair had synchronous population growth on an annual basis. Three species-pairs sharing trends were positively correlated with the AMO index which increased during the study period. Positive cycling of the AMO was correlated with increased temperature and precipitation in breeding areas of both continents, which may have produced favorable conditions (earlier springs, more ponds) for some duck populations. Differences in the local effects of weather on environmental conditions and other continent-specific extrinsic factors may mask annual synchrony in the response of continental populations to climate. Potential links between the AMO trends and extrinsic factors such as shared changes in anthropogenic drivers (e.g., climate and land use change) should be addressed in future studies.

Heterogenous resources across sagebrush type are associated with components of offspring fitness in an avian habitat specialist - Kyle A. Cutting; Emma C. Grusing; David Messmer; Sean R. Schroff; James A. Waxe; Aaron O'Harra; Bok F. Sowell (Biological Conservation, 2024)

Das fachdidaktische Wissen und Können von Sportlehrpersonen (PCK-Sport) - Jolanda Vogler; Roland Messmer; David Allemann (German Journal of Exercise and Sport Research, 2017)

Effects of climate change on coral grouper (Plectropomus spp.) and possible adaptation options - Morgan S. Pratchett; Darren S. Cameron; Jennifer Donelson; Louisa Evans; Ashley J. Frisch; Alistair J. Hobday; Andrew S. Hoey; Nadine A. Marshall; Vanessa Messmer; Philip L. Munday; Rachel Pears; Gretta Pecl; et al. (Reviews in Fish Biology and Fisheries, 2017)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Wheat yield and quality as influenced by reduced tillage in organic farming - Joséphine Peigné; Monika Messmer; Anne Aveline; Alfred Berner; Paul Mäder; Marina Carcea; Valentina Narducci; Marie-Françoise Samson; Ingrid K. Thomsen; Florian Celette; Christophe David (Organic Agriculture, 2014)